BEDA PENGARUH ECCENTRIC EXERCISE DAN PASSIVE STRETCHING PADA PENERAPAN ULTRASOUND TERHADAP PENURUNAN NYERI PENDERITA TENNIS ELBOW TIPE II DI KAMPUS JURUSAN FISIOTERAPI POLTEKKES MAKASSAR - Nurul Hikmah; Yonathan Ramba; Arpandjaman Arpandjaman (Media Fisioterapi Politeknik Kesehatan Makassar, 2021)
Background : Tennis Elbow is a complaint of pain in the forearm which usually radiates to the dorsum of the hand due to inflammation or non-specific degeneration of the extensor carpi radialis brevis (ECRB) muscle in the lateral epicondyle of the humerus. It is diagnosed clinically by the sensation of pain and tenderness over the lateral epicondyle of the humerus which is aggravated during dorsiflexion of the restricted wrist.Methods: This type of research is a quasi experiment with a ramdomized pre test-post test two group design. This study consisted of 2 sample groups, namely treatment group 1 which was given Eccentric Exercise and Ultrasound interventions and treatment group 2 which was given Passive Streaching and Ultrasound interventions. The sample of this study were students of the Makassar Health Ministry Polytechnic majoring in Physiotherapy who suffered from Type II Tennis Elbow with inclusion and exclusion criteria in sampling.Results: the mean value of tennis elbow in the First Treatment group (Ultrasound and Eccentric Exercise) is the value of P = 0.012 <0.05 where the pre test is 6.650 ± 1.046 and the post test is 4.150 ± 0.594 with an average difference of 4.49 ± 1.035 which means there is an increase the average Tennis Elbow is 4.49 after intervention (Ultrasound and Eccentric Exercise). The mean value of the Tennis Elbow pre test in the Treatment Two group (Ultrasound and Passive Stretching) had a value of P = 0.022 <0.05 and the pre test value was 4.180 ± 0.925 and the post test was 2.490 ± 1.080 with an average difference of 2.69 ± 1.178, which means that there was an average increase in Tennis Elbow by 2.69 after the intervention (Ultrasound and Passive Stretching). The results of the Mann-Withney test were p <0.05 which means that there was a significant difference in the mean between the first treatment group (Ultrasound and Eccentric Exercise) and the second treatment group (Ultrasound and Passive Stretching). This shows that Ultrasound and Eccentric Exercise are significantly more effective than Ultrasound and Passive Stretching in reducing VAS in Type II Tennis Elbow sufferers.Conclusion: Ultrasound Intervention and Eccentric Exercise have a more significant effect than Ultrasound and Passive Stretching on Reducing Pain in Patients with Type II Tennis Elbow.Keywords: Ultrasound, Eccentric Exercise, Passive Streaching, Type II Tennis Elbow.